Impact of Inflation on Purchasing Decisions of Residents of Selected Polish Voivodeships - Magdalena Wiercioch (Finanse i Prawo Finansowe, 2024)
The purpose of the article. The study aimed to assess the impact of an inflation level on purchasing decisions of consumers in selected voivodeships (mazowieckie, lubelskie, podkarpackie, małopolskie). The following hypotheses were adopted: